Parameters of Slavic morphosyntax - Franks, Steven (Oxford studies in comparative syntax., 1995)
Focusing on issues of case theory and comparative grammar, this study treats selected problems in the syntax of the Slavic languages from the perspective of Government-Binding theory. Steven Franks seeks to develop parametric solutions to related constructions among the various Slaviclanguages. A model of case based loosely on Jakobson's feature system is adapted to a variety of comparative problems in Slavic, including across-the-board constructions, quantification, secondary predication, null subject phenomena, and voice. Solutions considered make use of recent approaches tophrase structure,